Childhood cow's milk allergy and the risk of multiple sclerosis: a population based study - Ramagopalan, S; Dyment, D; Guimond, C; Orton, S; Yee, I; Ebers, G; Sadovnick, A (Elsevier, 2010)
Autoimmune mechanisms are thought to have a major role in the pathogenesis of multiple sclerosis (MS) and vitamin D is hypothesised to contribute to disease susceptibility. Cow's milk allergy (CMA) is a common childhood allergy arising from an immune system imbalance and can also lead to vitamin D deficiency due to dairy food avoidance. Here, we investigated whether or not CMA influences the subsequent risk to develop MS in a population-based cohort. We identified 6638 MS index cases and 2509 spousal controls with CMA information from the Canadian Collaborative Project on Genetic Susceptibility to MS (CCPGSMS). Frequency of CMA was compared between index cases and controls. No significant differences were found. Childhood CMA thus does not appear to be a risk factor for MS.